Nociones fundamentales del Realismo Jurídico - Campos Zamora, Francisco J. (2014)
In this article, we will put forward the main guidelines of legal realism as one of the most interesting responses given to the question: What is Law? We will look into the relation between legal realism and philosophical realism, and its three main trends: German legal realism, American legal realism and Scandinavian legal realism.